PENGARUH JUMLAH TAGIHAN DAN JUMLAH OBJEK YANG DIBAYAR TERHADAP PENERIMAAN PAJAK BUMI DAN BANGUNAN PERDESAAN DAN PERKOTAAN (PBB-P2) DI KABUPATEN GUNUNGKIDUL - Wawan Yulianto (Program Studi Manajemen Fakultas Ekonomi UST, 2018)
This research was aimed to test is there any influence between indepent variables (amount of claim and amount of objects paid to dependent variables (PBB-P2 revenue) both partially and simultaneously. The data was collected from Income and Management Finance and Aset’s District Departement in Gunungkidul regency, includes the amount of claim, amount of object paid, and PBB-P2 revenue. Methodology of this research was correlation with 54 data. The sample was selected by purposive sampling with the type of data used was the secondary archive of data, with the unit of data of subdistrict during three years. Before doing hypothesis testing, the data was analyzed first by classical asumption testing. Hypothesis testing was conducted with double linear regression statistical analysis device. The results of this research were as follows: (1) Testing partially showed that the amount of claim variable and the amount of object paid which was measured based on the Letter of Tax Object Notification has a significant and positive influence to PBB-P2 revenue. Testing simultaneously showed that the amount of claim and the amount of object paid which was measured based on SPPPT has a positive influence to PBB-P2 revenue.